Development of Human Resources in the Conditions of the Industrial Innovation-Driven Economy of Kazakhstan - BAITUOVA, Laura T.; SHAUKEROVA, Zina M.; AIKUPESHEVA, Dina М.; DOSKALIEVА, Bayan B. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The innovation-driven economy is often perceived as a part of refusal from the industrial relations and the increase in the capacity of the non-material production. Alongside with it, the increase in the capital requirements of production defined by the opportunities of recruiting the highest professional becomes relevant. The relevance of the paper is defined by the authors in the opportunity of speaking about the possibility of economic planning based on the forecast of the quality of human resources. The novelty of the research is in the fact that for the first time in the Post-Soviet history it considers the aspects of forming qualitative drivers of the economic development in the structure of the economic innovatization through the increase in its intellectual capacity. The authors define that is will help Kazakhstan to increase the investment attractiveness and to a greater extent adapt to the integration in the world economic system. The authors are developing here the methodical bases for the computation of the human resources in the economic environment based on the experience of the main countries-participants of the international economic exchange. The practical significance of the research is defined by the necessity and opportunity of establishing separate innovation-driven branches in the economy of Kazakhstan as a way of increasing the competitive advantage and formation of the branch of the international human resources.